Pemberdayaan Ibu-Ibu PKK Melalui Program Urban Farming di Kelurahan Rejosari Kota Semarang - Oktavia, Riska; Faqih, Ahmad; Riyadi, Agus (Jurnal SOLMA, 2025)
Background: The PKK community must be empowered through productive activities, such as urban farming, that will benefit the city as a whole. This programme has been implemented in RT/RW 01/05 Kelurahan Rejosari, Semarang. Method: The methods employed to empower PKK mothers include socialisation, training, mentoring, and monitoring. Results: The programme was initiated with an introductory phase that included socialisation and training, followed by the practical application of agricultural techniques such as plant cultivation in urban farming settings. This was followed by the provision of direct assistance to participants to address any challenges they encountered during the programme. The evaluation method is by monitoring the results of urban farming practices carried out by PKK mothers.The results obtained by PKK women are plant cultivation developed in urban farming practices, namely, chillies, eggplants, cassava, shallots, bitter melon, pandanus, melons, Brazilian spinach, celery, and orange leaves.In addition, the results of the women's plants are also used as a common garden and they apply in their respective homes. Conclusion: The present study investigates the impact of the PKK's empowerment through urban farming on the improvement of family welfare in Rejosari Village. The analysis indicates that the success of the programme is contingent on the active involvement of the community, the provision of support from the local government, and the continuity of mentoring and training.